Wallet Neuritis – An Example of Peripheral Sensitization - Siddiq, Md A. B.; Jahan, Israt; Masihuzzaman, SAM (Current Rheumatology Reviews, 2018)
Background: Wallet neuritis is an example of extra-spinal tunnel neuropathy concerning sciatic nerve. Its clinical appearance often gets confused with sciatica of lumbar spine origin. Wallet- induced chronic sciatic nerve constriction produces gluteal and ipsilateral lower extremity pain, tingling, and burning sensation. It was Lutz, first describing credit-card wallet sciatica in an Attorney, surfaced on Journal of American Medical Association (JAMA), 1978; however, the condition has not been well-studied in various other occupations. Case Summary: In this write-up, we take the privilege of demonstrating wallet neuritis as an example of peripheral sensitization in three different professionals' namely specialist doctor, driver, and banker first time in Bangladesh. All the three patients' demonstrated aggravated gluteal pain with radiation on the homo-lateral lower extremity while remained seated on heavy wallet for a while, fortunately improved discontinuing such stuff with. Alongside radical wallectomy, piriformis stretching exercise on the affected side had also been recommended and found worthy in terms of pain relief. Conclusion: long-standing use of rear pocket wallet may compress and sensitize ipsilateral sciatic nerve, generating features resembling lumbago sciatica; thereby, remains a source of patients' misery and diagnostic illusion for pain physicians as well.
Keywords: Wallet neuritis